Metabolic rewiring of isoniazid sensitivity in Mycobacterium tuberculosis - Erin R. Wang; Kevin Cho; Gregory A. Harrison; Stephanie R. Smelyansky; Vijay Soni; Asya Smirnov; Samuel R. McKee; George S. Ghabrial; Kelly N. Flentie; Wandy Beatty; Boatema Ofori-Anyinam; Souvik Sarkar; et al. (Proceedings of the National Academy of Sciences, 2025)
Isoniazid (INH) inhibits mycolic acid synthesis in Mycobacterium tuberculosis ( Mtb ) and is a cornerstone of treatment regimens against this deadly pathogen. However, over 10% of Mtb infections are INH-resistant. The compound C10 can sensitize clinically relevant INH-resistant mutants to killing by INH. Thus, understanding the mechanism of action for C10 could aid in designing new strategies for circumventing drug resistance. We find that C10 treatment reroutes carbon flux toward valine, drawing carbon away from gluconeogenesis and the TCA cycle. As a result, C10 decreases cell envelope capsule thickness and blocks an accumulation of peptidoglycan precursors that occurs in response to INH treatment in an INH-resistant Mtb katG mutant. In this altered metabolic state induced by C10, INH treatment of the INH-resistant Mtb katG mutant inhibits peptidoglycan synthesis, precipitating collapse of cell envelope integrity. Pyruvate supplementation relieves the C10-induced requirement for carbon flux toward valine, enhancing carbon assimilation into cell envelope precursors and restoring resistance to INH. In addition, we identify the formation of isoniazid-pyruvate in INH-treated katG W328L Mtb , where pyruvate sequesters INH, lowering the concentration of INH available to inhibit Mtb . Together, our findings reveal a bactericidal activity for INH in Mtb that can function in INH-resistant mutants independently of INH-mediated inhibition of mycolic acid synthesis. This activity for INH can be elicited by shifting carbon flux toward valine and away from cell envelope precursor synthesis, highlighting a metabolic vulnerability that can be exploited to kill INH-resistant Mtb .